The Influence of Brand Equity on the Purchase Decision of Samsung Smartphones (A Case Study of Consumers in Marpoyan Damai District, Pekanbaru City) - Ilham, Muhammad; Afifah, Dhiya Dwi (MUI Kota Pekanbaru, 2025)
The research was conducted to determine the influence of brand equity on purchasing decisions for Samsung brand smartphones, especially people who live in Marpoyan Damai District, Pekanbaru City. The research approach used quantitative methods by distributing questionnaires to 400 people using a random sampling method to answer the problem in this research using the following variables. Variables including the independent variables in this research are Brand Awareness, Brand Associations, Perceived Quality, Brand Loyalty, and the dependent variable is Purchase Decision. Data analysis uses descriptive analysis and multiple linear regression which is processed using SPSS version 26. The results of this research show: simultaneously brand equity has a significant influence on purchasing decisions, as shown by the results of the F test, the Fcount value is 13.198, while the Ftable value is 2.39. The probability significance value ɑ obtained is 0.00 < 0.05, while partially the variables from brand equity show significant results on purchasing decisions except for brand awareness and brand associations. It was also found that brand loyalty had the highest influence.